A taboo in healthcare; life support decisions at the terminal stage - Turgay Albayrak; Hilal Aksoy; Esra Meltem Koc; İrfan Sencan; Adem Ozkara (SERNEV, 2018)
Public who are the target audience of health caresystem need to be actively involved in the system for more effective healthcare provision. Advance directives which are the important examples ofparticipation in treatment decisions are written documents that, in thesituation of a serious illness, either clarify an individual's wishes forhealth care or determine a person to make health care decisions for thatindividual who becomes unable to do so. Living wills, health care power ofattorney, directive of do-not-resuscitate, withholding of life support andwithdrawing of life support are included in advance directives. Advancedirectives are being implemented in the United States of America (USA) and someEuropean countries. The legal status of advance directives vary by country.There is no data on the use and writing of advanced directives in our country.It is necessary to start discussing about people's decisions on terminal careand implementations by analyzing the material and moral broughts of patientcare at the end of life in both individual and social terms.